2017
DOI: 10.1002/ps.4630
|View full text |Cite
|
Sign up to set email alerts
|

Importance of prumycin produced by Bacillus amyloliquefaciens SD‐32 in biocontrol against cucumber powdery mildew disease

Abstract: This study demonstrates that prumycin is a major factor in SD-32's suppression of cucumber powdery mildew disease. Our findings shed light for the first time on prumycin's role in biocontrol by Bacillus against this disease. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 58 publications
3
23
0
1
Order By: Relevance
“…Similarly, B. subtilis and B. pumilus were the most effective bio-agent treatments for reducing AUDPC of squash powdery mildew (225.61 and 226.87, respectively) than the control (643.54), while there was insignificant difference of AUDPC in plants treated with T. harzianum, T. viridi, and B. chitinosporus. Obtained results are in agreement with the findings of many researchers who demonstrated that the bio-agents that were used in this study were effective for controlling powdery mildew disease (Kamel 2003;García-Gutiérrez et al 2013 andTanaka et al 2017). Previously, many studies demonstrated that Bacillus spp.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, B. subtilis and B. pumilus were the most effective bio-agent treatments for reducing AUDPC of squash powdery mildew (225.61 and 226.87, respectively) than the control (643.54), while there was insignificant difference of AUDPC in plants treated with T. harzianum, T. viridi, and B. chitinosporus. Obtained results are in agreement with the findings of many researchers who demonstrated that the bio-agents that were used in this study were effective for controlling powdery mildew disease (Kamel 2003;García-Gutiérrez et al 2013 andTanaka et al 2017). Previously, many studies demonstrated that Bacillus spp.…”
Section: Resultssupporting
confidence: 92%
“…Powdery mildew is the most serious disease that attacks squash plants and causes 30-50% of yield losses (El-Naggar et al 2012). The causal agent of cucurbit powdery mildew disease is Podosphaera xanthii, which is one of the most important limiting factors of cucurbit production all over the world (Tanaka et al 2017). Plant diseases are controlled by agreeable means, like resistant varieties, chemical fungicides, natural production, oils, and biological control (Hafez et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This extract inhibited pathogen growth on plate in low percentages (Sanchez et al 2019). Obtained results are in agreement with many researchers who found that the bio-agents studied were effective for controlling powdery mildew disease (Kamel 2003;García-Gutiérrez et al 2013;Tanaka et al 2017). Table 2 show that all tested treatments significantly reduced the percentage of the disease incidence and severity than the control.…”
Section: Podosphaera Xanthiisupporting
confidence: 89%
“…Bacillus spp. Are distinguished by high temperature tolerance, rapid growth in liquid cultures, ubiquity in soils, and it is considered a safe biocontrol agent to be applied (TANAKA et al, 2017). The mechanisms of control of the antagonist are diverse, standing out the process of antibiosis, competition, parasitism and predation.…”
Section: Introductionmentioning
confidence: 99%